Lange Jugendstrafen bei jugendlichen und heranwachsenden Gewalt- und Sexualstraftätern Eine Untersuchung des spezialpräventiven Charakters des (Jugend-)Strafvollzugs - Schmidt-Esse, Xenia (Universitätsverlag Göttingen, 2018)
The present work examines the execution of long youth penalties amongst juvenile and adolescent offenders convicted of violent and sexual crimes. To investigate the intention of the penal system, which lies in the social re-integration of prisoners to avoid further criminal behavior, different aspects like education, care, treatment, day-release and release preparation regarding young inmates were examined in detail. For this purpose, records obtained from Bundeszentralregister (Federal Central Criminal Register) as well as prison files of relevant offenders that were released from prison between 2002 and 2007 after completing a youth penalty of more than five years were evaluated. In addition, ministerial administrative provisions as well as a survey in penal institutions were used to analyze the current situation in prison.